THE ROLE OF UNESCO AS A WORLD HERITAGE CENTER IN THE ISSUES TOURISM PROJECTS IN KOMODO NATIONAL PARK REVIEWED FROM ENVIRONMENTAL CONCEPTS - Eni Susanti; Muhammad Nasir Badu; Sitti Mariah Ulfah (Asosiasi Dosen Muda Indonesia, 2022)
In this research, the author will show the role of UNESCO in Addressing the issue of developing tourism projects in Komodo National Park. As we know, UNESCO itself has designated National Parks Komodo is one of the world heritage sites with OUV standards (Outstanding Universal Value) or extraordinary universal value. Remembering the Park Komodo National is the habitat of various types of Komodo which only exist in Indonesia is also a conservation area, which needs to be protected and preserved. Regarding natural tourism management, of course it will provide the influence on a country in its tourism development, both positive or negative. The positive impact certainly needs to be maximized Negative impacts must be anticipated and controlled, if they threaten natural sites. For this reason, regarding this issue, this research aims to find out UNESCO's efforts as the World Heritage Center in responding to cases tourism development in Komodo National Park reviewed in concept Environmentalism. Role and influence is demonstrated through value protection universal extraordinary on world heritage sites, delivered by mail warning or appeal to the government or tourism project implementers in Komodo National Park. In this paper, the type of research used is qualitative. By using the deductive method, namely trying describes what general problems are being researched, the types of data used is secondary. Secondary data is data obtained from some literature such as books, internet based research (articles or journals and thesis), and also uses primary data through interviews.